Obtížná diferenciální diagnostika maligního melanomu - kazuistiky - Třešková, I; Pizinger, K; Kacerovská, D; Bursa, V; Kydlíček, T (Rozhledy v chirurgii, 2013)
Malignant melanoma is one of the most malignant tumours. If it is diagnosed in the early stage, the prognosis is quite good. Timely diagnosis is essential as well as early surgical removal of the tumour in a specialized centre. The aim of the article is to highlight the difficult diagnosis and differential diagnosis of malignant melanoma. The authors describe a rare case of malignant melanoma in an eleven-year-old girl, a neglected finding of malignant melanoma in a young man, the difficult differential diagnosis of malignant melanoma and a case of malignant melanoma arising from a congenital naevus.The incidence of malignant melanoma is increasing worldwide, and it is therefore necessary to bear this diagnosis in mind when performing clinical examination of patients and discovering suspected lesions.
Keywords: Child; Melanoma; dítě; Male; Diagnosis, Differential; lidé; Female; mužské pohlaví; ženské pohlaví; melanom; Humans; diferenciální diagnóza